LUDWIG WITTGENSTEIN: TOWARDS A MEANINGFUL TALK ABOUT RELIGION - Onos Godwin Idjakpo; peter.O.O. Ottuh (PREDESTINATION: Journal of Society and Culture, 2021)
Wittgenstein’s profound thought had rich implications regarding religious belief and religion. In his early philosophy, silence occupies a central place to articulate what is beyond the boundary of language. Silence overcomes the limits of human language. In Wittgenstein’s later philosophy, religious language and different religious languages are legitimized by the multiple uses of language. An evaluation of his linguistic philosophy and its application in religious belief reveals that despite the limitations of his philosophy, Wittgenstein has enriched the contemporary philosophy of religion. This paper discusses the meaningful talk about religion, religious speech acts and religious rituals with Wittgenstein’s later understanding of the religious domain. Though Wittgenstein was not a religious man, he saw things from a religious point of view. His insight on religious belief can be seen from different perspectives. From a pragmatic perspective, religious language is very much tied up with the form of life. It emerges from the everyday shared practices of the community of believers.